2018
DOI: 10.13057/asianjagric/g020102
|View full text |Cite
|
Sign up to set email alerts
|

Seed emergence and growth of the short age sugar palm (Arenga pinnata) as a response of seed scarification and liquid organic fertilizer application

Abstract: Elidar Y. 2018. Seed emergence and growth of the short age sugar palm (Arenga pinnata) as a response of seed scarification and liquid organic fertilizer application. Asian J Agric 2: 8-13. The research was aimed to know the effect of seed scarification and liquid organic fertilizer application to the seed emergence and growth of the short age sugar palm (Arenga pinnata (Wurmb.) Merr). The research was conducted at two experiments, i.e. (i) effect of seed scarification, and (ii) effect of liquid organic fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[54]. Another study on scarification of A.pinnata seeds revealed that scarification in the embryo part resulted in best germination percentage at around 99.81% [55]. These finding may help the farmers to synchronize germination and growth of A.pinnata seeds for plantation establishments of this multiutility palm.…”
Section: Seed Biology Of Arengasmentioning
confidence: 96%
“…[54]. Another study on scarification of A.pinnata seeds revealed that scarification in the embryo part resulted in best germination percentage at around 99.81% [55]. These finding may help the farmers to synchronize germination and growth of A.pinnata seeds for plantation establishments of this multiutility palm.…”
Section: Seed Biology Of Arengasmentioning
confidence: 96%